Optimasi Rute Distribusi Produk Minuman dan Makanan pada Distributor Nestle (CV Forward Kediri) dengan Algoritma Ant Colony Optimization - Allifira Andara Hasna; Bayu Rahayudi; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The distribution process at CV Forward Kediri involves more than one sales for the product delivery process. In this case, the route determination management from the distributor is very important so that the distribution process can be more optimal. The problem experienced by many salespeople in finding the closest route is known as the Multiple Traveling Salesman Problem. One of the optimization algorithms to solve the closest route-finding problem is the Ant Colony Optimization algorithm. This algorithm is algorithm that is inspired by groups of ant colonies in finding a path to get food. In this study, to determine the resulting solution from the Ant Colony Optimization algorithm, a comparison of the initial conditions with the system was carried out. By testing the parameters of Ant Colony Optimization, the optimal parameters are obtained, namely the iteration of 2000, the alpha value, the beta value of 0.1, the rho value of 0.3, and the tau value of 0.03. Based on the results of the comparison of the system using the Ant Colony Optimization algorithm, with an average fitness of 121.27 with the original condition of 179.42, it turns out that the results obtained by the system are much shorter than the original condition so that it can provide more optimal results.